2020
DOI: 10.1177/0954405420933705
|View full text |Cite
|
Sign up to set email alerts
|

Chatter identification in thin-wall milling using an adaptive variational mode decomposition method combined with the decision tree model

Abstract: Chatter is prone to occur in thin-wall part milling process due to the low stiffness and damping of the workpiece. It roughens the machining surface, shortens the tool life, and thus should be detected and prevented. However, the multimode and time-varying dynamics of thin-wall parts produces nonstationary and multicomponent cutting signals, which makes it challenging to accurately identify the chatter occurrence. In this article, an effective chatter identification method based on adaptive variationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The process uses a decision tree to calculate the chattering threshold after adaptive variational mode decomposition divides the original signal into many sub-signals. The results of the experiments demonstrated that the approach can accurately and successfully identify chatter [5]. Jin et al proposed a stability prediction method based on a dynamics model.…”
Section: Related Workmentioning
confidence: 98%
“…The process uses a decision tree to calculate the chattering threshold after adaptive variational mode decomposition divides the original signal into many sub-signals. The results of the experiments demonstrated that the approach can accurately and successfully identify chatter [5]. Jin et al proposed a stability prediction method based on a dynamics model.…”
Section: Related Workmentioning
confidence: 98%
“…Cyclostationary-based indicators were proposed in the angular domain from the periodic and residual parts of angular speed and cutting force signals for chatter detection, and the indicator based on IAS is recommended as it does not require additional sensors [84]. The application of adaptive variational mode decomposition for chatter detection has been lately reported in [142] and [198]. Mishra and Singh [87,[340][341][342][343]] investigated a spline-based local mean decomposition technique, while Zhang et al [137] used a morphological empirical wavelet transform (EWT).…”
Section: Time-frequency Domain Analysismentioning
confidence: 99%
“…Entropy features represent the signal randomness and complexity. Some of them have been reported for chatter detection, including permutation entropy (PE) [134,157], Rényi entropy (RE) [162], Sample entropy (SampEn) [133,142,186], approximate entropy (ApEn) [88,133,169,170,183] and dispersion entropy [151]. Tran et al [154] utilized fuzzy entropy for feature selection.…”
Section: Feature Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al [15] successfully employed a long short-term memory network to analyse features extracted through wavelet packet decomposition of in-process acoustic emission signals for the assessment of grinding wheel condition. And to increase the robustness of chatter identification in thin-walled milling processes, an issue caused by highly dynamic and complex workpiece-tool interactions, Wang et al [16] developed an adaptive time-frequency domain feature selection process. In conjunction with a decision tree model, the authors were able to detect chatter with an accuracy of 92.42%.…”
mentioning
confidence: 99%